2009
DOI: 10.1002/cmdc.200800355
|View full text |Cite
|
Sign up to set email alerts
|

SHOP: A Method For Structure‐Based Fragment and Scaffold Hopping

Abstract: A new method for fragment and scaffold replacement is presented that generates new families of compounds with biological activity, using GRID molecular interaction fields (MIFs) and the crystal structure of the targets. In contrast to virtual screening strategies, this methodology aims only to replace a fragment of the original molecule, maintaining the other structural elements that are known or suspected to have a critical role in ligand binding. First, we report a validation of the method, recovering up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…The fact that the property space of the binding cavities does not completely match the property space of the ligands has intriguing implications for ligand-based and structure-based design of novel ligands in drug discovery programs, since it indicates that ligands could be developed with very different binding modes from those of known ligands. One way to address this possibility would be to use fragment-based screening methods, either virtual ( e.g ., hot spot approaches) or experimental ( e.g ., nuclear magnetic resonance screening), to explore binding cavities and identify such potential ligands 6769…”
Section: Resultsmentioning
confidence: 99%
“…The fact that the property space of the binding cavities does not completely match the property space of the ligands has intriguing implications for ligand-based and structure-based design of novel ligands in drug discovery programs, since it indicates that ligands could be developed with very different binding modes from those of known ligands. One way to address this possibility would be to use fragment-based screening methods, either virtual ( e.g ., hot spot approaches) or experimental ( e.g ., nuclear magnetic resonance screening), to explore binding cavities and identify such potential ligands 6769…”
Section: Resultsmentioning
confidence: 99%
“…SBs are interpreted as different structures depending on chirality (L, D or undefined) and position in the peptide (N-terminal, C-terminal, in the middle). For each SB, additional information is stored in the database such as InchiKey and Inchi, 2D structure, atom mapping and connectivity, physico-chemical properties and pharmacophoric properties described through molecular descriptors calculated by VolSurf [ 29 ] and SHOP software [ 30 ] ( Fig 3 ). Each connection of SBs is annotated by two connected structural blocks, bond type and two connected atoms which help to identify the direction of the connection.…”
Section: Methodsmentioning
confidence: 99%
“…Several investigations have demonstrated that simple molecular fingerprint descriptors are suitable for scaffold hopping [159][160][161], sometimes also combined with machine-learning methods [162,163]. Several approaches have been proposed based on the idea to replace a central scaffold of a molecule by novel scaffolds having the same exit vectors [164][165][166][167], and, depending on the approach, pharmacophore or property field similarity of the novel scaffold to the known reference scaffold.…”
Section: Data Mining For Promising Library Design Starting Pointsmentioning
confidence: 99%